Histological Evaluation of Gentamicin-Associated Myocardial Alterations in Adult Male Rats - Al-Jubouri, Nawras Ali Hussein; Shaheed, Dhurgham Qasim (American Journal of Biology and Natural Sciences, 2026)
In order to understand how gentamicin affects the histology of the adult rat myocardium and its possible uses in clinical medicine, this study sought to investigate the effects of gentamicin administered over a period of time on adult rat myocardium by utilizing H and E stained sections evaluated by light microscopy. Gentamicin is widely used in human medicine as an aminoglycoside antibiotic which is effective against Gram-negative bacteria. Because aminoglycosides are potentially toxic to renal and auditory systems of mammals, many previous investigations have demonstrated that gentamicin, in particular, causes both nephrotoxicity and ototoxicity. However, despite the fact that gentamicin produces systemic toxicities to both kidneys and inner ears, very few studies have assessed whether gentamicin induces toxic changes to cardiac muscles of animals. Two sets of six adult male albino rats approximately 200-250 grams each were selected through random sampling. One group of rats (controls) received 14 consecutive intraperitoneal injections of normal saline throughout the duration of the experiment. The second group of rats (treated with gentamicin), received 14 consecutive intraperitoneal injections of gentamicin at a dosage of 31 mg/kg/day during the duration of the experiment. Once the experiment had concluded, both sets of rats were euthanized. Both sets of rats provided samples of ventricular myocardium (cardiac muscle). The samples were processed per standard laboratory procedure. Following sample processing the samples were sliced to produce thin cross-sections. Each cross-section was stained with H and E. All slices were observed with a microscope using a 40 X power lens. Once all samples were analyzed it was determined that the cross-sectional areas of cardiac muscle from control rats had well-defined elongated cardiac muscle fibers, large elongated nuclei, and regular spacing between individual cardiac muscle fibers. Conversely, cross-sectional areas of cardiac muscle from rats treated with gentamicin exhibited differences relative to those of control rats. Specifically, cross-sectional areas of cardiac muscle from rats treated with gentamicin included separation of individual cardiac myocytes; significantly larger than normal inter-cellular/inter-muscular spaces within the myocardium; smaller than normal coarseness of myocardial bundles; and slight disruption/distortion of the typical myocardial architectural design. These findings suggest that chronic exposure to gentamicin in male adult rats resulted in detectable histological changes to rat myocardium. Further biochemical/morphometric/immunohistochemical studies will be needed to evaluate the functional and molecular mechanisms that contribute to the previously identified changes in rat myocardium after gentamicin exposure.